2016
DOI: 10.3390/w8040137
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Impact of River Barrage Construction on Stream-Aquifer Interactions, Korea

Abstract: This study investigated changes in stream-aquifer interactions during the period shortly after the construction of the Changnyeong-Haman River barrage (CHRB) on the Nakdong River in South Korea. The hydraulic diffusivity (α) and river resistance (R) values at the semipervious stream-aquifer interface were estimated by using a one-dimensional (1-D) analytical solution with Fourier transform (FT). Prior to the application of the 1-D analytical solution, the noise effects on the groundwater levels were removed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The geology of the study area (Figure 3) is composed of Cretaceous sedimentary rocks of the Hayang Group and Cretaceous volcanic rocks (mainly Jusan andesite) of the Yucheon Group belonging to the Gyeongsang Supergroup, with the intrusion of Cretaceous Bulguksa igneous rocks, including diorite, biotite granite, granodiorite, granite porphyry, and dikes [34][35][36]. Quaternary alluvial layers chiefly occurring along the river area are composed of clay, sand, gravel and weathered layers, in descending order, with an average thickness of 7.9 m, 9.1 m, 5.6 m and 5.1 m, respectively [20]. Cretaceous sedimentary rocks mainly consist of purple shale, grey shale, greenish-grey sandstone/sandy shale, and purple sandy shale.…”
Section: Geological and Hydrological Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The geology of the study area (Figure 3) is composed of Cretaceous sedimentary rocks of the Hayang Group and Cretaceous volcanic rocks (mainly Jusan andesite) of the Yucheon Group belonging to the Gyeongsang Supergroup, with the intrusion of Cretaceous Bulguksa igneous rocks, including diorite, biotite granite, granodiorite, granite porphyry, and dikes [34][35][36]. Quaternary alluvial layers chiefly occurring along the river area are composed of clay, sand, gravel and weathered layers, in descending order, with an average thickness of 7.9 m, 9.1 m, 5.6 m and 5.1 m, respectively [20]. Cretaceous sedimentary rocks mainly consist of purple shale, grey shale, greenish-grey sandstone/sandy shale, and purple sandy shale.…”
Section: Geological and Hydrological Settingsmentioning
confidence: 99%
“…Numerous researchers have studied the relationship between groundwater and surface water [17][18][19][20][21][22][23][24][25]. Oh et al [21] examined the effects of the construction of Changnyeong-Haman River barrage in Korea on the interaction between rivers and aquifers.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the logarithmic mean values of estimated river resistance obtained from all four observation wells are similar and that they are close to the lumped value of R = 2491.3 m and of a similar order of magnitude as values in the literature. For example, Ha et al (2007) found that the river resistance in the Mangyeong River of Korea could be as high as ~1,700 m. Oh et al (2016) found that the river resistance in the Nakdong River of Korea was ~5,000 m.…”
Section: 1029/2018wr024639mentioning
confidence: 99%
“…Groundwater levels rose in most areas near the rivers because river levels increased due to the management level of the weirs [1]. Consequently, weir construction helped to meet water demands and increased flood protection [2][3][4]. However, concerns about the impact of the restricted rivers on the riparian ecosystem remained [5,6]; therefore, nine weirs have operated periodically for natural ecosystem recovery, from 2017.…”
Section: Introductionmentioning
confidence: 99%